Longevity pathways and memory aging - Gkikas, Ilias; Petratou, Dionysia; Tavernarakis, Nektarios (Frontiers in Genetics, 2014)
The aging process has been associated with numerous pathologies at the cellular, tissue, and organ level. Decline or loss of brain functions, including learning and memory, is one of the most devastating and feared aspects of aging. Learning and memory are fundamental processes by which animals adjust to environmental changes, evaluate various sensory signals based on context and experience, and make decisions to generate adaptive behaviors. Age-related memory impairment is an important phenotype of brain aging. Understanding the molecular mechanisms underlying age-related memory impairment is crucial for the development of therapeutic strategies that may eventually lead to the development of drugs to combat memory loss. Studies in invertebrate animal models have taught us much about the physiology of aging and its effects on learning and memory. In this review we survey recent progress relevant to conserved molecular pathways implicated in both aging and memory formation and consolidation.